Facies heterogeneity and lobe facies multiscale analysis of deep-marine sand-shale complexity in the west crocker formation of sabah basin, nw borneo - Jamil, M. (MDPI AG, 2021)
Deepwater lobes constitute a significant volume of submarine fans and are primarily believed to exhibit a simple sheet geometry. However, recent studies interpret the geometries of these deep-marine lobes as distinct with respect to the complexity of the facies and their distribution. Hence, a conceptual model of deep-marine sediments is essential to discuss the deep-marine sediments associated with the fan and lobe architecture. The present study highlights the facies heterogeneity and distribution of various lobe elements at a multiscale level by considering a case study of the West Crocker Formation of Sabah in northwest Borneo. The formation was logged on a bed-to-bed scale from recently well-exposed sections, with a total vertical thickness of more than 300 m. The lithological characteristics, bed geometry, sedimentary textures and structures of individual beds were used to categorize the rock units into nine sedimentary lithofacies: five sandstone lithofacies (S1âS5), one hybrid bed facies (H), two siltstone facies (Si1 and Si2) and one shale or mudstone facies (M). These facies were grouped into four facies associations (FA1âFA4), which were interpreted as lobe axis (FA1), lobe off-axis (FA2), lobe fringe (FA3) and distal fringe to interlobe (FA4) facies associations. This study is applicable for the distribution of lobes and their subseismic, multiscale complexities to characterize the potential of hydrocarbon intervals in deep-marine sand-shale system around the globe. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.